Optimizing the Geometric Structure of a Thermoelectric Cooler with Multi-objective Constraint - Zhang Xiaobo; Xu Xiangguo (Zhileng xuebao)
The influences of the geometric parameters of a thermoelectric cooler on its cooling capacity and COP have been previously investigated under assumptions of a constant input current and fixed temperatures of hot/cold ends. However, in this paper, constant external heat exchanging conditions, instead of constant temperatures of hot/cold ends, were assumed, and the influence of each geometric parameter (number of thermo-couples and the ratio of the length of a thermo-element to its cross-sectional area) on the cooling capacity, COP, and cold end temperature were analyzed. The physical implications of each effect are given in detail, revealing the coupling between these parameters. Based on the analyses, in addition to the constraints of the cooling capacity, the COP, and cold end temperature on the selection of the geometry parameters considered, a novel design diagram was developed for choosing the best geometric structure of thermoelectric coolers with a multi-objective constraint. This diagram can obtain the optimal geometry parameters under different requirements both quickly and clearly. For example, under the boundary conditions set in this paper, when the cold end temperature is 280 K and the cooling capacity is 15 W, there is an optimal solution to the geometric parameters. However, when the cold end temperature is 240 K and the cooling capacity is 100 W, there are no geometrical parameters that can satisfy both the cold end temperature and the cooling requirements.